Perceptions of Garment Workers on Retraining and Skill Development to Adapt to the Requirements of the Fourth Industrial Revolution (A Case Study of the VSIP Industrial Park - Hai Phong) - Thu Trang, Nguyen; Huyen Trang, Vu (VNU Journal of Science: Policy and Management Studies; Vol 40 No 4, 2024)
The rapid improvement of automated equipment and innovative production lines needs increased worker awareness and the development of adaptive abilities, which are critical for determining the competitive competence of enterprises in the sector. This study investigates the perspectives of garment industry workers on retraining and skill development activities to meet the needs of the Fourth Industrial Revolution (IR 4.0). The study collected information from 117 people who now work in the VSIP industrial parks in Hai Phong. The research looks at the following significant aspects: i) Employees' understanding of the need for retraining; ii) Employees' perspectives on the critical skills necessary to meet Industry 4.0 requirements; and iii) Barriers to accessing and participating in training programs. The findings show that, while employees in the garment sector recognize the importance of retraining and skill development, several individuals need help accessing these programs due to time constraints, financial constraints, and a lack of information about training opportunities. The study emphasizes the need to develop training programs that combine technical competence with interpersonal skills and establish support networks from businesses and organizations that assist workers (such as unions and job placement centers).